Analysis of Integration-Based Learning on Research and Community Service at Islamic Religious Education Study Program - Mahariah Mahariah; Muslem Muslem; Siti Ardianti (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objective of this study was to examine the incorporation of research and community service into the learning process as a means of enhancing the attainment of outcome-based learning. The research was carried out at the Islamic Religious Education Study Programme, State Islamic University of North Sumatra, located in Medan. The research primarily centres around the implementation process, barriers encountered, and initiatives aimed at enhancing the proficiency of lecturers. The research informants comprised instructors and students who served as executors, as well as heads of faculties and study programmes who assumed managerial roles. The research employed a qualitative methodology utilising a case study technique. Gathering data through the utilisation of observation techniques, interviews, and documentation. The process of data analysis involved three key stages: data reduction, data display, and conclusion. The study findings elucidate that the incorporation of research and community service into learning manifests through learning methodologies, academic culture, lecture materials and references, media, and learning evaluation. The obstacles in implementation are to challenges in working with leaders, inadequate student facilities, and difficulty in disseminating student learning outcomes. To surmount these challenges, the leadership implemented various initiatives, including offering training, disseminating policies, and conducting supervision and monitoring.